(untitled) (Neliniini Kolyvannya, 2025)
We propose an analytical method for solution of the spatial dynamic problem of propagation of elastic vibrations in a circular bounded plate under the action of instantaneous internal dilation ε^* (instantaneous relative change in an infinitesimal volume) arising, for example, as a result of contact welding of plates This problem arose in connection with the problem of decoding acoustic emission signals in the process of prediction of the residual resource of hazardous industrial welded metal objects under operating conditions using acoustic emission systems, in which piezoelectric sensors of a circular shape are used.